2019
DOI: 10.1016/j.compstruct.2019.01.101
|View full text |Cite
|
Sign up to set email alerts
|

Strain rate effect on the mechanical behavior of polyamide composites under compression loading

Abstract: This paper presents an experimental study on the effect of strain rate on the compressive behavior of polyamide composites. Contrary to thermoset woven reinforced composites, thermoplastic woven reinforced composites have always received less interest despite its excellent damage and impact resistances. In this context, this work aims to study the behavior of fiber reinforced thermoplastic composites submitted to high strain rate in compression. The tested material is a thermoplastic composite made of armor ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Both the compressive strength and modulus were found to increase with increasing strain rates, and the compressive strain to failure was approximately insensitive to strain rates. Massaq et al [ 35 ] investigated the compressive mechanical response of PA6/glass composite in the transverse and longitudinal fibers directions at strain rates from 10 to 2500 s . Positive rate-sensitivity for the elastic modulus and failure stress were observed and the loading direction, viz.…”
Section: Introductionmentioning
confidence: 99%
“…Both the compressive strength and modulus were found to increase with increasing strain rates, and the compressive strain to failure was approximately insensitive to strain rates. Massaq et al [ 35 ] investigated the compressive mechanical response of PA6/glass composite in the transverse and longitudinal fibers directions at strain rates from 10 to 2500 s . Positive rate-sensitivity for the elastic modulus and failure stress were observed and the loading direction, viz.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the release of fillers from polymer composites could be related to intrinsic failure mechanism. Release of rGO either as protruding or as free-standing from the PA6-rGO composite, during the abrasion process, could be explained by an interfacial debonding between the rGO and PA6 molecules or an adhesive failure as a result of the weak interaction between the rGO and PA6 matrix, as reported by previous studies (Massaq et al, 2019;Zaman et al, 2012;Zheng et al, 2019;. In addition, failure of graphene sheets is also highly possible, i.e., graphene layer breakage.…”
Section: Qualitative Detection Of Rgo Released From the Pa6 Matrixmentioning
confidence: 55%
“…In their simulations they used the value of 0.1 referring to experimental data; however, they also reported their initial research, where the friction coefficient varied in the range of 0.1 to 1, and the results changed by 6%. Friction reduction can be achieved by applying grease to the sample surface; its impact can also be taken into account analytically, as in [34]. In [19], a geometrically advanced RVE model with additional reinforcement in the z axis is shown; however, the authors point out technical problems with contact.…”
Section: Numerical Studiesmentioning
confidence: 99%